Tumour growth inhibition and systemic responses of ΔsopBΔsopDΔpipD disrupted Salmonella Agona and Salmonella Typhimurium in mice - Naem Zia, Ubaidah Naim Taraq; Amar Ng, Emy Sarah Ng; Sidik, Mohd Amirudin; Mohd Idris, Mohamad Fauzi; Khoo, Chai Hoon; Sukardi, Sabrina; Yeap, Swee Keong; Cheah, Yoke Kqueen (Universiti Putra Malaysia, 2021)
Introduction: Bacteria had long been known to have tumour-targeting and tumour inhibition capabilities and have re-emerged into the limelight of cancer research as a possible alternative treatment for solid tumours. Conventional therapies for solid tumours are either by surgery, chemotherapy, radiotherapy, which are very invasive and non-specific to the tumours and results in various adverse effects on the patients. Bacterial Mediated Tumour Therapy often utilises attenuated bacteria as therapeutic agents to ensure reduced pathogenicity of the strains. However, this often results in lower invasiveness towards the tumours itself. In this study, we studied the tumour inhibition capabilities of Salmonella Pathogenicity Island (SPI) attenuated Salmonella Typhimurium (S. Typhimurium) and Salmonella Agona (S. Agona), specifically with attenuation of sopB, sopD, and pipD genes. Methods: Balb/c mice bearing CT26 tumours were inoculated with S. Typhimurium and S. Agona, both unattenuated and ΔsopBΔsopDΔpipD attenuated strains. Tumour volumes were monitored daily. Organs and blood were collected for plasma liver enzyme analysis and histopathology studies on testis, liver, kidneys and brain. Results: The ΔsopBΔsopDΔpipD S. Agona treated group showed improved inhibition of tumour growth with 51.11% tumour volume reduction compared to unattenuated S. Agona. The ΔsopBΔsopDΔpipD strains have also shown lesser systemic effects as observed in plasma and histopathological studies) compared to its unattenuated counterparts. Conclusion: The present study showed that ΔsopBΔsopDΔpipD S. Agona has a great potential to be utilised as tumour therapeutic agent as it exerts lesser systemic effect while having similar tumour inhibition capabilities as the well-studied S. Typhimurium strain.